Bacteria communities and water quality parameters in riverine water and sediments near wastewater discharges - Carolina Oliveira de Santana; Pieter Spealman; Daniella Azulai; Mary Reid; M. Elias Dueker; Gabriel G. Perron (Scientific Data, 2022)
Measurement(s) temperature of water • conductivity of water • dissolved oxygen in water • salinity of water • Concentration of Escherichia coli in water • Concentration of total coliforms in water • Concentration of Enterococcus sp. • Concentration of endotoxins in water • Relative abundance of integron 1 in water • Bacterial 16S RNA Technology Type(s) YSI field probe • Colilert dection system • Enterolert dection system • Charles River Endosafe system • quantitative PCR • Illumina Sequencing Sample Characteristic - Organism Bacteria Sample Characteristic - Environment Fresh water river Sample Characteristic - Location United States